Impact of different guidewires on the implantation depth using the largest self-expandable TAVI device - Veulemans, Verena; Wilde, Nihal; Wienemann, Hendrik; Adrichem, Rik; Hokken, Thijmen W.; Al-Kassou, Baravan; Shamekhi, Jasmin; Mauri, Victor; Maier, Oliver; Jung, Christian; Horn, Patrick; Adam, Matti; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background The deployment process of the largest self-expandable device (STHV-34) during transcatheter aortic valve implantation (TAVI) might be challenging due to stabilization issues. Whether the use of different TAVI-guidewires impact the procedural success and outcome is not well known. Therefore, we sought to evaluate the impact of non-Lunderquist (NLu) versus the Lunderquist (Lu) guidewires during TAVI using the STHV-34 on the procedural and 30-day outcomes. Methods The primary study endpoint was defined as the final implantation depth (ID) depending on the selected guidewire strategy. Key secondary endpoints included VARC-3-defined complications. Results The study cohort included 398 patients of four tertiary care institutions, of whom 79.6% (317/398) had undergone TAVI using NLu and 20.4% (81/398) using Lu guidewires. Baseline characteristics did not substantially differ between NLu and Lu patients. The average ID was higher in the Lu cohort (NLu vs Lu: -5.2 [-7.0-(-3.5)] vs. -4.5 [-6.0-(-3.0)]; p=0.022*). The optimal ID was reached in 45.0% of patients according to former and only in 20.1% according to nowadays best practice recommendations. There was no impact of the guidewire use on the thirty-day outcomes, including conduction disturbances and pacemaker need (NLu vs Lu: 15.1% vs. 18.5%; p=0.706). Conclusion The use of the LunderquistTM guidewire was associated with a higher ID during TAVI with the STHV-34 without measurable benefits in the 30-day course concerning conduction disturbances and associated pacemaker need. Whether using different guidewires might impact the outcome in challenging anatomies should be further investigated in randomized studies under standardized conditions.